Pembatasan Hak Bagi Mantan Terpidana Korupsi Menjadi Calon Kepala Daerah - Donal Fariz (The Constitutional Court of the Republic of Indonesia, 2020)
Election as an instrument of elite circulation actually creates another problem, namely corruption. A strict of legal instrument is needed to arrange nominations for candidates for public officials, one of which is the head of the region in order to obtain qualified candidates with integrity to be elected by voters. One form is by limiting the rights of former convicted corruption cases to be able to run for candidates for regional head. These restrictions are permitted conceptually and are emphasized through a number of decisions of the Constitutional Court. Research questions in this paper consist of: first, how are the problems of corruption and democracy that occur in Indonesia? Second, how are the concepts and regulation on the right of politics? Third, how are the development of the decisions of the Constitutional Court related to the right for former convicts of corruption to run for candidates as regional heads? This research uses the normative juridical method.